Computed Tomographic Blend Sign Is Associated With Computed Tomographic Angiography Spot Sign and Predicts Secondary Neurological Deterioration After Intracerebral Hemorrhage. Issue 1 (January 2017) - Sporns, Peter B.; Schwake, Michael; Schmidt, Rene; Kemmling, André; Minnerup, Jens; Schwindt, Wolfram; Cnyrim, Christian; Zoubi, Tarek; Heindel, Walter; Niederstadt, Thomas; Hanning, Uta
Abstract : Background and Purpose—: Significant early hematoma growth in patients with intracerebral hemorrhage is an independent predictor of poor functional outcome. Recently, the novel blend sign (BS) has been introduced as a new imaging sign for predicting hematoma growth in noncontrast computed tomography. Another parameter predicting increasing hematoma size is the well-established spot sign (SS) visible in computed tomographic angiography. We, therefore, aimed to clarify the association between established SS and novel BS and their values predicting a secondary neurological deterioration. Methods—: Retrospective study inclusion criteria were (1) spontaneous intracerebral hemorrhage confirmed on noncontrast computed tomography and (2) noncontrast computed tomography and computed tomographic angiography performed on admission within 6 hours after onset of symptoms. We defined a binary outcome (secondary neurological deterioration versus no secondary deterioration). As secondary neurological deterioration, we defined (1) early hemicraniectomy under standardized criteria or (2) secondary decrease of Glasgow Coma Scale of >3 points, both within the first 48 hours after symptom onset. Results—: Of 182 patients with spontaneous intracerebral hemorrhage, 37 (20.3%) presented with BS and 39 (21.4%) with SS. Of the 81 patients with secondary deterioration, 31 (38.3%) had BS and SS on admission. Multivariable logistic regression analysis identified hematoma volume (odds ratio, 1.07 per mL; P ⩽0.001), intraventricular hemorrhage (odds ratio, 3.08; P =0.008), and the presence of BS (odds ratio, 11.47; P ⩽0.001) as independent predictors of neurological deterioration. Conclusions—: The BS, which is obtainable in noncontrast computed tomography, shows a high correlation with the computed tomographic angiography SS and is a reliable predictor of secondary neurological deterioration after spontaneous intracerebral hemorrhage.